Seasons of Syn. (19th November 2019) - Hunter‐Cevera, Kristen R.; Neubert, Michael G.; Olson, Robert J.; Shalapyonok, Alexi; Solow, Andrew R.; Sosik, Heidi M.
Abstract: Synechococcus is a widespread and important marine primary producer. Time series provide critical information for identifying and understanding the factors that determine abundance patterns. Here, we present the results of analysis of a 16‐yr hourly time series of Synechococcus at the Martha's Vineyard Coastal Observatory, obtained with an automated, in situ flow cytometer. We focus on understanding seasonal abundance patterns by examining relationships between cell division rate, loss rate, cellular properties (e.g., cell volume, phycoerythrin fluorescence), and environmental variables (e.g., temperature, light). We find that the drivers of cell division vary with season; cells are temperature‐limited in winter and spring, but light‐limited in the fall. Losses to the population also vary with season. Our results lead to testable hypotheses about Synechococcus ecophysiology and a working framework for understanding the seasonal controls of Synechococcus cell abundance in a temperate coastal system.